Socio-environmental factors influencing the consumption of soft drinks in South Africa. - Leckram, Sandya. (My University, 2014)
ABSTRACT Background: According to the OECD FACTBOOK 2011, 42.4% of South Africa’s population is overweight and obese, with women at a higher risk at 54.9%, than men at 29.8%. Various reasons have been cited for high obesity levels in South Africa. According to (Lowell 2004), these include genetics, modern lifestyles and most importantly, food. In particular, the fast-food industry has been singled out as being able to entice people, especially young children at schools, through marketing campaigns designed to make people eat more food. The consumption of soft drinks in particular, has grown substantially over the past 10 years (The Coca-Cola Company 2013). Very few studies have been conducted in South Africa among adolescents that focus on several lifestyle behaviours related to soft drink consumption. The intention of this research is to establish the association between soft drink consumption and socio-environmental factors such as physical activity, television viewing and family rules, in adolescents. Methods: The data are part of a quantitative survey conducted amongst 311 parents or primary caregivers of adolescents between 10 and 19 years of age in Gauteng. This resulted in a final sample of 624 respondents. Binary logistic regression was used to test the association between soft drink consumption physical activity, television viewing and family rules (restriction and obligation rules). The key findings: The results of this study show that there is an association with soft drink consumption and watching television daily during a meal amongst both boys and girls. There were positive associations amongst girls for no obligation rules, and no association with lack of physical activity amongst both boys and girls.
MBA 2013
Keywords: Carbonated beverages,Consumer behavior,Consumers' preferences,Soft drink industry.